1998
DOI: 10.1093/jnci/90.2.118
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Adhesion of Prostate Cancer Cells to a Human Bone Marrow Endothelial Cell Line

Abstract: Background:In virtually all patients with advanced prostate cancer, the disease metastasizes to bone and causes osteoblastic growth. However, the mechanisms that contribute to bone metastasis are poorly understood. It has been hypothesized that the bone provides a favorable growth environment for prostate cancer cells, which nonselectively seed the bone marrow from the bloodstream. Alternatively, prostate cancer cells may preferentially bind to bone marrow endothelial cells. We developed an in vitro model of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
159
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(165 citation statements)
references
References 27 publications
4
159
2
Order By: Relevance
“…It has been shown that prostate epithelial cells interact directly with the BME cells, initially via selectins and this interaction is then stabilised by integrin binding (Orr et al, 2000). These are not the only binding steps, since antibodies to CD11a, CD18, LFA-1 and CD31 have also been shown to interfere with the binding process (Lehr and Pienta, 1998). Once bound, prostate epithelial cells induce endothelial cell retraction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that prostate epithelial cells interact directly with the BME cells, initially via selectins and this interaction is then stabilised by integrin binding (Orr et al, 2000). These are not the only binding steps, since antibodies to CD11a, CD18, LFA-1 and CD31 have also been shown to interfere with the binding process (Lehr and Pienta, 1998). Once bound, prostate epithelial cells induce endothelial cell retraction.…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3, VCAM-1, CD11a, CD18, integrins and LFA-1 have been implicated in prostate cancer adhesion to bone derived endothelial cells. 28 Alpha-2 beta-1 and alpha-3 beta-1 were responsible for prostate cancer cell adhesion to collagen I, and these integrins' expression was upregulated in prostate cancer cells with TGF-beta treatment (Table 3). 37,38 To study the mechanisms involved in bone metastases, several animal models are under development.…”
Section: Resultsmentioning
confidence: 99%
“…Using antibodies, Lehr and Pienta were able to reduce PC-3 cell adhesion with galactose rich modi®ed citrus pectin and the following antibodies: galectin-3, vascular cell adhesion molecule (VCAM), CD11a (alpha-L), CD18 (beta-2), and leukocyte functional antigen-1 (LFA-1) (Figure 3). 28 Another study showed that galectin-3 is expressed on the surface of a variety of rodent microvessel endothelium, and a subsequent study in our lab showed that PC-3 cells expressed galectin-3 (Pacis et al, manuscript submitted). 29 This data suggests that the galectin-3, VCAM, alpha-L, beta 2, and LFA-1 all may play partial role in tumor cell adhesion to HBME-1.…”
Section: Cell Adhesionmentioning
confidence: 93%
See 2 more Smart Citations